The Chilean agricultural transformation during the second half of the twentieth century: A story of institutional change - Antonio Saravia (Institute for Advanced Development Studies (INESAD), 2008)
The second half of the twentieth century witnessed a dramatic transformation of the Chilean agricultural sector. From accounting for only five percent of the value of Chile's total exports in the late 1960s, agricultural exports grew to account for more than 30 percent of this value in the mid 1990s. Using a modified neoclassical growth formulation, we show that the transformation of the Chilean agricultural sector can be associated with institutional changes or modifications to the sector's basic functioning structure. In particular, our historical review shows that changes in the definition of property rights over land, caused by the Chilean agrarian reform first and the general economic reform later, seem to have greatly caused the changes in the sector's levels of investment and production.
Keywords: N56; O13; Q11; Q15; 330; Institutional Economics; Property Rights; Land Tenure; Agricultural; Economics; Chile; Landwirtschaftliche Entwicklung; Agrarverfassung; Agrarstruktur; Chile